The heritable path of human physical performance: from single polymorphisms to the "next generation" - Santos, C. G. M.; Pimentel-Coelho, P. M.; Budowle, B.; de Moura-Neto, R. S.; Dornelas-Ribeiro, M.; Pompeu. F. A. M. S.; Silva, R. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Human physical performance is a complex multifactorial trait. Historically, environmental factors (e.g., diet, training) alone have been unable to explain the basis of all prominent phenotypes for physical performance. Therefore, there has been an interest in the study of the contribution of genetic factors to the development of these phenotypes. Support for a genetic component is found with studies that shown that monozygotic twins were more similar than were dizygotic twins for many physiological traits. The evolution of molecular techniques and the ability to scan the entire human genome enabled association of several genetic polymorphisms with performance. However, some biases related to the selection of cohorts and inadequate definition of the study variables have complicated the already difficult task of studying such a large and polymorphic genome, often resulting in inconsistent results about the influence of candidate genes. This review aims to provide a critical overview of heritable genetic aspects. Novel molecular technologies, such as next-generation sequencing, are discussed and how they can contribute to improving understanding of the molecular basis for athletic performance. It is important to ensure that the large amount of data that can be generated using these tools will be used effectively by ensuring well-designed studies.